How Motivation Affects Productivity in the Workplace - Sri Endarti Halim; Mansyur (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The research team at PT PLN (Persero) Customer Service Executor (UP3) in Makassar Selatan set out to measure the effectiveness of motivation in boosting worker productivity. Quantitative methods are employed in this study. All 182 people now employed at PT. PLN (Persero) UP3 Makassar Selatan constitute the research population. The slovin method was used to select a sample size of 65 respondents. Primary data, collected from the responses to the survey, is used for this analysis. Data will be analyzed using multiple linear regression, t tests, f tests, and the coefficient of determination test in addition to a descriptive statistical analysis, validity test, reliability test for normality, multicollinearity, and heteroscedasticity, and hypothesis testing. Employees at PT PLN (Persero) Customer Service Executor (UP3) in Makassar Selatan were shown to benefit from both internal and external motivation, according to the findings of this study. Furthermore, the study's findings demonstrate that both internal and external motivation have a substantial impact on performance at PT PLN (Persero) Customer Service Executor (UP3) Makassar Selatan.